Expert Sistem Untuk Mendiagnosa Penyakit Ayam Menggunakan Metode Forward Chaining - Silvilestari Silvilestari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Chicken is one of the most desirable types of birds for breeding. However, the maintenance of any kind of chicken tended to be prone to attack by various diseases. This situation resulted in a chicken farmer has a high dependence on veterinarian or chicken expert. That requires that information technology expert system that can help diagnose diseases of chicken and can be used anywhere and anytime. In this study designed a web-based expert system that is able to diagnose and provide solutions for chicken diseases. Inference method used is a forward chaining and using search techniques depth first search. This expert system will show choice of symptoms which can be chosen by user, where each choice of symptoms will lead the user to the next choice of symptoms until get the final results. At the final results, the expert system displays the name of the disease is diagnosed, symptoms, description of disease, and disease solutions